PENGARUH KUALITAS WEBSITE (WEBQUAL 4.0) DAN KUALITAS PELAYANAN (SERVQUAL) ONLINE TO OFFLINE (O2O) COMMERCE TERHADAP KEPUASAN PELANGGAN DAN MINAT PEMBELIAN ULANG - Tisia Priskila; Angel Priskila (Jurnal Manajemen, 2019)
The development of the e-commerce industry in Indonesia has recently accelerated. But behind that, there are problems that continue to overshadow such as the problems of logistics and infrastructure of Indonesia in meeting market demand, the number of unbanked consumers, and the tendency of consumers to preview the goods before shopping. Those are the factor of consumers' reluctance to repurchase at e-commerce. Therefore, the O2O commerce concept that combines online and offline transaction channels is believed to be able to answer the challenges currently faced by e-commerce. The customer repurchase intention and customer satisfaction of O2O commerce is believed to be influenced by website quality and online service quality. This research was conducted with the aim to determine the effect of website quality (WebQual 4.0) and service quality (ServQual) of O2O commerce on customer satisfaction and repurchase intention. The analysis technique used in this study is SEM-PLS (Structural Equation Modeling - Partial Least Square) with a sample of 100 respondents. The results showed that website quality and service quality of O2O commerce had a significant positive effect on customer satisfaction and repurchase intention.